Strategy for Increasing Solid Waste Levy Revenue in Ogan Ilir Regency, South Sumatera Province - Permatasari, Rosmalinda; Firda, Ani (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
Solid waste management (SWM) is still a big challenge for cities around the world, especially in rapidly developing metropolitan cities in developing countries, one of which is in South Sumatera Province. This province consists of several regencies and cities that already have their own waste management systems. Ogan Ilir Regency is one of the districts that has its own waste management system, but it has not run effectively because the waste retribution has not been optimally implemented. This writing paper aims to analyze potential sources of waste retribution, analyze aspects of willingness to pay and recommend new amounts of waste retribution in accordance with existing circumstances. The research method used is in the form of surveys, observations and interviews with the intended respondents. The new levy analysis is based on Regulation Number 7 of the Indonesian Minister of Home Affairs (Permendagri) for 2021. The findings revealed that there were various possible waste retributions emanating from the market sector of IDR 437,635,000, however only IDR 85,144,500 were realized. The willingness to pay study results suggest that education level and income have a large influence on the readiness to pay for waste retribution. The newly obtained levy is IDR 237,922 per ton for the recommended outcomes. The new levy analysis is based on Regulation Number 7 of the Indonesian Minister of Home Affairs (Permendagri) for 2021. The findings revealed that there were various possible waste retributions emanating from the market sector of IDR 437,635,000, however only IDR 85,144,500 were realized. The availability to contribute study results suggests that education level and income have a large influence on the readiness to spend money on waste retribution. The newly obtained levy is IDR 237,922 per ton for the recommended outcomes.